Gaps in protection to Anopheles exposure in high malaria endemic regencies of Papua Province, Indonesia - Ismail E. Rozi; Lepa Syahrani; Dendi H. Permana; Puji B. S. Asih; Maria E. Sumiwi; Neil F. Lobo; William A. Hawley; Din Syafruddin (PLoS ONE, 2025)
Background Malaria in eastern Indonesia remains high despite significant reductions and local elimination in other parts of the country. Malaria control activities that have been implemented include early diagnosis and prompt treatment, provision of Long-lasting insecticide-treated nets (LLINs), and indoor residual spraying (IRS). To expedite malaria elimination in this region, a rapid entomological assessment combined with human behaviour observations (HBOs) were conducted in eight high malaria endemic regencies in Papua Province, Indonesia. The present study focuses on identifying gaps in protection against mosquito biting indoors and outdoors that may contribute to the sustained transmission and persistently high endemicity. Methods This research was carried out alongside a rapid entomological assessment across 48 villages in all eight regencies over 150 days. It included human landing catches (HLCs) of adult mosquitoes, with human behavior recorded through direct observation during these HLCs. The human behavior observation (HBO) data concentrated on temporal (overnight) and spatial (domestic or peri-domestic) presence, in addition to bed net usage and sleeping patterns. Household surveys, which were also conducted during the entomological collections, gathered information on house construction materials, mosquito bite prevention practices, livestock presence, and other intervention usage. Results Behavior-adjusted exposure for unprotected individuals in 14 villages shows gaps in protection of ITN usage before sleeping. Meanwhile, an analysis of household survey in each regency identified several gaps in protection against mosquito bites. Human exposure to mosquito bites was driven by ITN usage, IRS coverage, indoor presence without protection prior to sleeping, the absence of mosquito house screens, and outdoor presence without protection. Conclusions The data reveals several gaps in protection against mosquito exposure across all eight regencies of Papua assessed. There is a need to optimize indoor interventions, as current vector control efforts do not adequately address outdoor exposure. Assessing spatial and temporal exposure can help identify effective protective vector strategies for these areas while highlighting persistent exposure risks. Community-based larval source management could enhance overall exposure reduction. Additionally, innovative measures like spatial repellents may address some protective gaps, together with improved case detection and treatment. The findings indicate that the existing strategy may not suffice to eradicate malaria in the region, necessitating a reconsidered, evidence-based, and adaptive approach.